Enhancing Social and Academic Success for High-Functioning Autism Spectrum Disorder Students in Tertiary Education - I. Kocurova-Giurgiu; M. Loffelmannova (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
This review examines integrating social thinking principles and Theory of Mind development to support high-functioning autism spectrum disorder (ASD) students in tertiary education. We present an evidence-based framework for enhancing social and academic outcomes, drawing from developmental research, cognitive psychology, and higher education practices. The paper highlights social cognition's crucial role in academic success, providing implementation strategies for university settings while addressing unique challenges and opportunities for adult ASD learners.